Associations Between Peer Victimization and Academic Performance - Espelage, Dorothy L.; Hong, Jun Sung; Rao, Mrinalini A.; Low, Sabina (Theory into practice)
This article reviews the extant literature on the links between peer victimization and academic performance and engagement among children and adolescents. Although most of the research on this association is based on cross-sectional investigations, research using longitudinal designs is starting to point to the fact that peer victimization does impact changes in academic performance over time. This research also points to several mediators and moderators that explain the association between repeated victimization and academic challenges, including peer rejection, depression, and decreases in students' sense of school belonging. Teachers and administrators should address peer victimization through programs and frameworks such as positive behavior intervention supports and social-emotional learning approaches. These programs decrease aggression and victimization, increase peer acceptance and social competence, and improve academic engagement and test scores.